(untitled) (Biodiversitas Journal of Biological Diversity, 2022)
Abstract. Koneri R, Nangoy MJ, Maabuat PV, Saroyo, Wakhid. 2022. Diversity and composition of butterflies in three habitats around Rayow Waterfall, Minahasa District, North Sulawesi, Indonesia. Biodiversitas 23: 1091-1098. Butterflies play an important role in ecosystems as pollinating agents, and their beautiful colors have a high potential for ecotourism activities. This study aims to analyze the diversity and composition of butterflies on three habitats around Rayow Waterfall, Minahasa District, North Sulawesi, Indonesia, which might be developed as ecotourism paths for butterfly-watching. Butterfly sampling using the sweeping technique was conducted on ecotourism paths in three habitat types: residential, agroforestry, and waterfall. Each ecotourism path consisted of three transect lines with a length of each transect of 300 m. The results showed 5 families of butterflies consisting of 56 species and 943 individuals. The most common family and species found were Nymphalidae and Eurema tominia (Snellen van Vollenhoven, 1865), and the highest abundance, number, and diversity index were found in agroforestry habitat. Meanwhile, the composition of butterflies differed significantly across the three habitats. Waterfall habitat was characterized by high relative humidity and low air temperature, while the high air temperature characterized residential habitat. The highest diversity of butterflies was found in the agroforestry habitat, and this was because of the complex vegetation structure that supported the survival of butterflies. The result of this study can serve as baseline information for the development of butterfly-based tourism programs in the Rayow Waterfall.